2020
DOI: 10.1089/end.2020.0149
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Threshold for Ablation During Holmium Laser Lithotripsy: How High Can You Go?

Abstract: Purpose: We performed in vitro studies to assess the relationship of pulse frequency on stone ablation during contact laser lithotripsy and determine if there is a threshold after which its effect on lithotripsy is limited. Methods: BegoStones were fragmented using a Ho:YAG laser (P120 Moses) and a 230 lm fiber at 0.5 J on long pulse (LP) and Moses distance (MD) modes in contact with the stone. The relationship between the number of pulses (1-40 Hz) on stone crater volume was assessed using three-dimensional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
3
19
0
2
Order By: Relevance
“…This feature can be seen from the distinct shift of the optimal v fiber from 3.5 mm/s to 4.1 mm/s under SD = 0.25 mm, and from 0.5 mm/s to 3.5 mm/s under SD = 0.50 mm when the bubble collapse toward the stone surface was eliminated. This observation is consistent with previous studies, in which a faster scanning speed (e.g., 3 mm/s vs. 1 mm/s) was found to produce higher dusting efficiency regardless of PRF in contact mode (13). Under similar settings (0.5 J, 20 Hz) using another laser lithotripter with different pulse profiles, the maximum dusting efficiency could be achieved at even higher v fiber of 10 mm/s (23).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This feature can be seen from the distinct shift of the optimal v fiber from 3.5 mm/s to 4.1 mm/s under SD = 0.25 mm, and from 0.5 mm/s to 3.5 mm/s under SD = 0.50 mm when the bubble collapse toward the stone surface was eliminated. This observation is consistent with previous studies, in which a faster scanning speed (e.g., 3 mm/s vs. 1 mm/s) was found to produce higher dusting efficiency regardless of PRF in contact mode (13). Under similar settings (0.5 J, 20 Hz) using another laser lithotripter with different pulse profiles, the maximum dusting efficiency could be achieved at even higher v fiber of 10 mm/s (23).…”
Section: Discussionsupporting
confidence: 93%
“…Conventional theory in the past two decades attributes photothermal ablation and microexplosion to be the dominant mechanisms of stone damage in LL (2,9,10). As a result, previous studies often advocate placing the fiber tip in contact with the stone surface, i.e., SD = 0 mm, with the hope to maximize laser energy transmission and treatment efficiency (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aldouki et al [ 23 ] found that MD had the highest ablation and fragmentation rates both at 0 and 1 mm distance when compared to the rest of the Lumenis’ PMs. In another article, the same authors found better stone ablation with MD than with SP, especially at a fiber moving speed of 3 mm/s rather than 1 mm/s [ 25 ].…”
Section: Resultsmentioning
confidence: 99%